PREVENTIVE MAINTENANCE USING RELIABILITY CENTRED MAINTENANCE (RCM): A CASE STUDY OF A FERROCHROME MANUFACTURING COMPANY - Fore, S.; Msipha, A. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: High productivity in industry requires high equipment reliability and plant availability. The aim of this paper is to illustrate the management of preventive maintenance by application of the Reliability Centred Maintenance (RCM), targeting a ferrochrome processing plant. The research points out that preventive maintenance is often neglected, affecting process continuity, and thus compromising product quality due to drops and fluctuations in operating temperature. These breakdowns tend to be frequent and longer, thus affecting production targets. Start-up failures are also experienced after carrying out maintenance. The maintenance department is affected by the unpredictability of the equipment